Influence of polynucleosome preparation methods on sedimentation velocity analysis of chromatin. (22nd December 2016) - Kujirai, Tomoya; Machida, Shinichi; Osakabe, Akihisa; Kurumizaka, Hitoshi
Abstract : Chromatin dynamics and higher order structures play essential roles in genomic DNA functions. Histone variants and histone post-translational modifications are involved in the regulation of chromatin structure and dynamics, cooperatively with DNA methylation and chromatin binding proteins. Therefore, studies of higher-order chromatin conformations have become important to reveal how genomic DNA is regulated during DNA transcription, replication, recombination and repair. The sedimentation velocity analysis by analytical ultracentrifugation has been commonly used to evaluate the higher-order conformation of in vitro reconstituted polynucleosomes, as model chromatin. Three major preparation methods for the unpurified, purified, and partially purified polynucleosomes have been reported so far. It is important to clarify the effects of the different polynucleosome preparation methods on the sedimentation profiles. To accomplish this, in the present study, we prepared unpurified, purified and partially purified polynucleosomes, and compared their sedimentation velocity profiles by analytical ultracentrifugation. In addition, we tested how the histone occupancy affects the sedimentation velocities of polynucleosomes. Our results revealed how free histones and polynucleosome aggregates affect the sedimentation velocity profiles of the polynucleosomes, in the absence and presence of Mg 2+ ions.